Intermediate layer as measure against rolling bearing creep. Issue 6 (23rd February 2018) - Schiemann, T.; Pörsch, S.; Leidich, E.; Sauer, B.
Abstract: Rolling bearings are a part of every wind‐turbine transmission. In terms of bearing design, the bearing rings are of particular interest. The current trend for increasing power and dynamic stress, together with the associated increases in specific loads, have brought creep―an irreversible relative motion between bearing rings and shafts or housings―to the forefront. Creep leads to wear and can cause shaft displacements with serious consequences for the meshing of teeth in gearboxes, for example. In fact, many insurance companies cite the creep of bearing rings as one of the main causes of wind‐turbine gearbox failures. This article presents a complex kinematic 3D FE multi‐body simulation of a rolling bearing. This simulation makes a detailed analysis of the relative motion or creep of bearing rings possible for the first time. It also presents options, based on materials technology and design, for reducing or eliminating creep in existing systems or at the product‐development phase. The 2 key solutions, both based on an additional layer between bearing and housing, that show best results are presented within this article. This gives the user specific information for optimizing the bearing structure with respect to the choice of bearing and bearing ring design to ensure that future damage is prevented.